Household Accounting – A Case of Subsidised Self-Employed Entrepreneurs in Slovenia - Rant, Damjana; Horvat Robert; Tominc, Polona; Korošec Bojana (Naše gospodarstvo/Our economy, 2017)
This paper presents the results of the first empirical study of household accounting in Slovenia, which was conducted on a sample of households of subsidised self-employed entrepreneurs. Based on an original measurement of the levels of household accounting, this study presents the scope of different accounting components in these households. Further, it gives the results of the comparison between those subsidised self-employed entrepreneurs who managed to keep their business and those who failed to do so. The comparison of the results showed a statistically significant difference between the two groups of entrepreneurs only in terms of the scope of monitoring of household costs and expenditures.